American College of Rheumatology White Paper on Antimalarial Cardiac Toxicity. Issue 12 (26th October 2021) - Desmarais, Julianna; Rosenbaum, James T.; Costenbader, Karen H.; Ginzler, Ellen M.; Fett, Nicole; Goodman, Susan; O'Dell, James; Pineau, Christian A.; Schmajuk, Gabriela; Werth, Victoria P.; Link, Mark S.; Kovacs, Richard
Abstract : Hydroxychloroquine (HCQ) and chloroquine (CQ) are well‐established medications used in treating systemic lupus erythematosus and rheumatoid arthritis, as well as skin conditions such as cutaneous lupus erythematosus. In rare cases, arrhythmias and conduction system abnormalities, as well as cardiomyopathy, have been reported in association with HCQ/CQ use. Recently, however, the corrected QT interval (QTc)–prolonging potential of these medications, and risk of torsade de pointes (TdP) in particular, have been highlighted in the setting of their experimental use for COVID‐19 infection. This report was undertaken to summarize the current understanding of HCQ/CQ cardiac toxicity, describe QTc prolongation and TdP risks, and discuss areas of priority for future research. A working group of experts across rheumatology, cardiology, and dermatology performed a nonsystematic literature review and offered a consensus‐based expert opinion. Current data clearly indicate that HCQ and CQ are invaluable medications in the management of rheumatic and dermatologic diseases, but they are associated with QTc prolongation by directly affecting cardiac repolarization. Prescribing clinicians should be cognizant of this small effect, especially in patients taking additional medications that prolong the QTc interval. Long‐term use of HCQ/CQ may lead to a cardiomyopathy associated with arrhythmias and heart failure. Risk and benefit assessment should be considered prior to initiation of any medication, and both initial and ongoing risk–benefit assessments are important with regard to prescription of HCQ/CQ. While cardiac toxicity related to HCQ/CQ treatment of rheumatic diseases is rarely reported, it can be fatal. Awareness of the potential adverse cardiac effects of HCQ and CQ can increase the safe use of these medications. There is a clear need for additional research to allow better understanding of the cardiovascular risk and safety profile of these therapies used in the management of rheumatic and cutaneous diseases.